2015
DOI: 10.1007/s00737-015-0512-5
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study and pilot randomised trial of an antenatal depression treatment with infant follow-up

Abstract: Substantial evidence links antenatal depression, anxiety and stress with negative effects on foetal development, resulting in enduring problems in child development. Despite this, there is a paucity of research on intervention programmes designed to address depression and anxiety, and none that include infant outcomes. We aimed to evaluate the efficacy of a brief treatment for maternal depression and anxiety in pregnancy in a sample of women with a diagnosed depressive disorder. We developed a cognitive behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
139
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(142 citation statements)
references
References 64 publications
(62 reference statements)
1
139
0
1
Order By: Relevance
“…(): PSA and PSS Milgrom et al. (): EPDS and a Structured Clinical Interview for DSM‐IV (SCID). From an initial sample of 169 women referred to the study with an EPDS score of 12 or more, 54 (32%) women were finally eligible and consented to participate in a SCID.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(): PSA and PSS Milgrom et al. (): EPDS and a Structured Clinical Interview for DSM‐IV (SCID). From an initial sample of 169 women referred to the study with an EPDS score of 12 or more, 54 (32%) women were finally eligible and consented to participate in a SCID.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies evaluated psychological interventions including: CBT (Bittner et al., ; Milgrom et al., ); CBA (Brugha et al., ) and MCBT (Faramarzi et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies reported significant difficulties enrolling and retaining pregnant or postpartum women in Cognitive Behavioral Therapy (CBT) (Carter et al, 2005; McKee et al, 2006). As a result, recent studies have modified CBT to improve feasibility and acceptability among pregnant women (McGregor et al, 2014; Milgrom et al, 2015; O’Mahen et al, 2013). For example, O’Mahen and colleagues (2013) utilized an engagement interview followed by modular sessions delivered in a flexible format (home or clinic) with an “active outreach strategy” to retain participants.…”
Section: Introductionmentioning
confidence: 99%
“…For example, O’Mahen and colleagues (2013) utilized an engagement interview followed by modular sessions delivered in a flexible format (home or clinic) with an “active outreach strategy” to retain participants. Milgrom and colleagues (2015) modified their CBT based intervention for pregnancy by changing from 12 group sessions to 8 individual sessions. Both studies showed promise in increasing engagement and retention into psychotherapy and in effectively reducing depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%